Molecular and Low-Resolution Structural Characterization of the Na+-Translocating Glutaconyl-CoA Decarboxylase From Clostridium symbiosum - Vitt, Stella; Prinz, Simone; Hellwig, Nils; Morgner, Nina; Ermler, Ulrich; Buckel, Wolfgang (Frontiers in Microbiology, 2020)
Some anaerobic bacteria use biotin-dependent Na+-translocating decarboxylases (Bdc) of β-keto acids or their thioester analogues as key enzymes in their energy metabolism. Glutaconyl-CoA decarboxylase (Gcd), a member of this protein family, drives the endergonic translocation of Na+ across the membrane with the exergonic decarboxylation of glutaconyl-CoA (ΔG0´ ≈ -30 kJ/mol) to crotonyl-CoA. Here, we report on the molecular characterization of Gcd from Clostridium symbiosum based on native PAGE, size exclusion chromatography (SEC) and laser-induced liquid bead ion desorption mass spectrometry (LILBID-MS). The obtained molecular mass of ca. 400 kDa fits to the DNA sequence-derived mass of 379 kDa with a subunit composition of 4 GcdA (65 kDa), 2 GcdB (35 kDa), GcdC1 (15 kDa), GcdC2 (14 kDa), and 2 GcdD (10 kDa). Low-resolution structural information was achieved from preliminary electron microscopic (EM) measurements, which resulted in a 3D reconstruction model based on negative-stained particles. The Gcd structure is built up of a membrane-spanning base primarily composed of the GcdB dimer and a solvent-exposed head with the GcdA tetramer as major component. Both globular parts are bridged by a linker presumably built up of segments of GcdC1, GcdC2 and the 2 GcdDs. The structure of the highly mobile Gcd complex represents a template for the global architecture of the Bdc family.